FORMULATION AND EVALUATION OF ORAL SELF EMULSIFYING DRUG DELIVERY SYSTEM OF LORNOXICAM - C. APARNA; C. APARNA; DR.PRATHIMA SRINIVAS; DR. K.S.K. RAO PATNAIK (International Journal of Pharma and Bio Sciences, 2015)
The objective of the present study is to formulate Self emulsifying drug delivery system (SEDDS) of lornoxicam, an anti-inflammatory drug to sustain the drug release and to reduce the side effects. The study involves combining oils with food grade non ionic emulsifiers to form concentrates that can incorporate large quantities of water and remain as a single phase liquid. Solubility studies were performed to select oils, surfactants and co-surfactants for the formulation of the drug (BCS class II). In this study, self emulsifying formulations (Batch F1 to F20) of drug Lornoxicam were made using different concentration of Capryol 90, Tween 20, Tween 80, Transcutol P, Propylene glycol. Systematic optimization was carried out, with a goal to minimize self emulsification time, to sustain the percentage drug release and reduce the side effects. The best emulsification grade was with batch F9. The in vitro drug release of Lornoxicam SEDDS was sustained (87.12% for 24 hours) when compared to marketed formulation Lornoxi (tablet) (100% at 90 mins). Pharmaco dynamic studies performed by paw volume method indicated significant (p< 0.05) inhibition in paw edema (75%) for the test formulation after 4hours as compared to the standard formulation (56%).